The learner’s own language - Kerr Philip (ExELL (Explorations in English Language and Linguistics))
The learner’s own language (commonly referred to as ‘L1’ or ‘first language’) has been neglected as a resource in the learning of another language and, in some contexts, it has been banned altogether. The arguments in favour of own-language exclusion are not supported by research and the policy is not followed by a majority of teachers. A reconsideration of these arguments and an awareness of practical suggestions for drawing on the learners’ own language as a resource for learning may help language teachers to enrich their repertoire of teaching techniques and activities.